Peningkatan Hasil Belajar Matematika Pada Materi Perkalian Dengan Penerapan Metode Jarimatika Pada Kelas II SD - Lintang Kusuma Wardani; Oktaviana Dwi Rahmadhani; Diana Ermawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to explain the increase in mathematics learning outcomes in multiplication material by applying the Jarimatika method in class II at SD 2 Panjunan. Data collection techniques in this research used observation, interview and documentation techniques. The method used in this research is classroom action research, the research subjects are teachers and class II students at SD 2 Panjunan. The instruments of this research are interview sheets, observation sheets and learning results test sheets. The data analysis technique used in this research is quantitative and qualitative data analysis. This research uses the Kemmis and Mc Taggart model research design, where each cycle or round consists of several stages which include planning, action, observation and reflection. The results of this research show that the application of the Jarimatika method with multiplication material can improve mathematics learning outcomes for class II students at SD 2 Panjunan as many as 26 student. This can be proven based on the results of the presentations from cycle I and cycle II. In cycle I there were 12 students who were declared complete with a percentage of 46% and there were 14 students who did not complete with a percentage of 54%. In cycle II there were 23 students who were declared complete with a percentage of 88% and 3 students had not yet completed with a percentage of 11%. So it can be stated that the learning outcomes of cycles I and II have increased by 85%. The conclusion of this research is that applying the Jarimatics method can improve mathematics learning outcomes in multiplication material for class II students.